2009
DOI: 10.1248/yakushi.129.735
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pharmacists in a Community Pharmacy for Self-Medication of Patients with Headache

Abstract: Pharmacists in a community pharmacy may recommend an over-the-counter (OTC) drug to patients with headache. However, it is not clear how pharmacists should distinguish the symptoms of patients and facilitate appropriate self-medication. Here, we investigated the role of pharmacists in a community pharmacy in recommending OTC drugs for self-medication by patients with headache and elucidated their future needs using a questionnaire intended for doctors and pharmacists. More than half of the pharmacists surveyed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 4 publications
0
4
0
2
Order By: Relevance
“…2 Headache is the commonest cause for use of analgesic self-medication in this study and pharmacist was one of the major source of information of self-medication. Naito et al 20 in their study observed that pharmacist in community pharmacy recommending drugs for headache and elucidated future needs using a questionnaire intended for doctors and pharmacists. More than 50% pharmacists were not having any experience with recommending Over The Counter (OTC) drugs for patients with headache, hence they were not able to give proper guidance about need of physician visit or OTC medication and recommended use of assistance tool to diagnosis headache like screener for migraine and guidelines for chronic headache.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Headache is the commonest cause for use of analgesic self-medication in this study and pharmacist was one of the major source of information of self-medication. Naito et al 20 in their study observed that pharmacist in community pharmacy recommending drugs for headache and elucidated future needs using a questionnaire intended for doctors and pharmacists. More than 50% pharmacists were not having any experience with recommending Over The Counter (OTC) drugs for patients with headache, hence they were not able to give proper guidance about need of physician visit or OTC medication and recommended use of assistance tool to diagnosis headache like screener for migraine and guidelines for chronic headache.…”
Section: Discussionmentioning
confidence: 99%
“…More than 50% pharmacists were not having any experience with recommending Over The Counter (OTC) drugs for patients with headache, hence they were not able to give proper guidance about need of physician visit or OTC medication and recommended use of assistance tool to diagnosis headache like screener for migraine and guidelines for chronic headache. 20 The factors that influence self-medication are patient satisfaction with the healthcare provider, cost of the drugs, educational level, socioeconomic factors, age and gender. 10 In this study, decreased healthcare cost and education level are the factors observed that can affect self-medication of analgesics.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] However, pharmacists need guidelines and training to improve their patient counselling skills, especially those needed for basic emergencies. 4 No articles published from 1995-2009 were found in PubMed that matched the following search criteria: pharmacy students, emergencies/emergency situations, and training/education.…”
Section: Introductionmentioning
confidence: 99%
“…Both doctors and pharmacists thought that pharmacists should not only provide patients with "instruction on the use of drugs" but also suggest "when to consult a hospital or clinic". 31 However, strategies may need to be devised to motivate patients to do this, as another Japanese survey of pharmacists and doctors found that 22% of pharmacists had experienced refusal by patients with headache to consult a clinic, despite the pharmacist's recommendation. 32 Community pharmacists have an important role in supporting patients with headache.…”
Section: A Multidisciplinary Approachmentioning
confidence: 99%